Enhancing Students' Courtesy Through Group Counseling: The Role of Role-Playing Techniques - Mahmudah, Mutia; Kurniawan, Wisnu; Rizal, Agus; Djanah, Miftahul (Indonesian Journal of Learning Education and Counseling, 2025)
This study explains and describes how effective group counseling using role-playing techniques is in significantly improving courtesy attitudes for students, and provides a solution to the problematic gap in character education research. This research uses a quantitative approach with a pre-experiment method, one of which is the design used with One Group Pre-Test and Post-Test Design. The research sample was taken from class VIII Mts Riyadlatul Fallah consisting of 10 students selected through purposive sampling, based on the low level of politeness. Data were collected using politeness questionnaire and analysed using Wilcoxon test in SPSS v22. The results showed a significant increase in students' politeness scores, from a pre-test average of 60.7 to a post-test average of 78.1 (p < 0.05). This shows that group counselling with role-playing techniques is effective in improving students' politeness. This study suggests that role-playing techniques can be further used in group counselling services to encourage students' character development at school.